Absorption Capacity, Innovative Culture, and Organizational Innovation: Role of Catur Purusa Artha Culture as Moderating - Utami, Ni Made Satya; Verawati, Yenny; Irwandika, Gede (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This research aimed to investigate the relationship between absorptive capacity (ACap) and innovative culture (ICul) in an organization. Additionally, the impact of ICul on innovation and the mediating function of the variable were analyzed. In this context, Catur Purusa Artha (CPA) culture served as a moderating varaible in assimilating organizational innovation (OIn).Design/Methodology/Approach: A quantitative design was applied, and data were collected using a questionnaire distributed to 350 Small and medium enterprises (SMEs) units. Subsequently, the collected data were investigated using the Smart PLS3 application.Research findings: The results showed that ACap did not affect OIn. ACap had a positive and substantial impact on ICul, which was influenced by OIn. Therefore, ICul functioned as a mediating variable in the relationship between ACap and OIn. CPA was reported to moderate the relationship between ACap and OIn.Theoretical Contribution/Originality: The literacy could be used as a management practice developed in the business actors of Bali Province. In this context, the role of local culture was important in running a business.Practitioners/Policy Implications: This research could be used in an organization for social, economic, cultural, and business development. The observation data and the conclusion were used as a reference.Research Limitations/Implications: SMEs managers in Bali Province were used as samples since some organizations did not implement the local CPA culture. Furthermore, a national organizational culture could be applied to various sectors.